2019
DOI: 10.1002/ddr.21569
|View full text |Cite
|
Sign up to set email alerts
|

Novel steroid sulfatase inhibitors based on N‐thiophosphorylated 3‐(4‐aminophenyl)‐coumarin‐7‐O‐sulfamates

Abstract: In the present work, we described convenient methods for the synthesis of N‐thiophosphorylated 3‐(4‐aminophenyl)‐coumarin‐7‐O‐sulfamates as steroid sulfatase (STS) inhibitors. To design the structures of the potential STS inhibitors, molecular modeling techniques were used. A computational docking method was used to determine the binding modes of the synthesized inhibitors as well as to identify potential interactions between specified functional groups on the inhibitors and the amino acid residues present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Fluorinated-, 4-aminophenyl-N-phosphorylated-and N-thiophosphorylated-7-O-sulphamate-3-arylcoumarins (compounds 63, 64 and 65 respectively) have been studied by the same research group, showing more than 10 times higher inhibitory potency than coumarin-7-O-sulfamate as inhibitors of STS. Amongst the studied compounds, the most interesting proved to be compound 63, both displaying IC 50 values of 0.27 µM [148], a similar IC 50 of approximately 0.20 µM for the phosphorylated derivatives (compounds 64 and 65) [149,150]. Supported by molecular modelling techniques, fluorinated compound 66 has been designed, synthetized and then tested, proving to display an IC 50 of 0.18 µM against STS, and an IC 50 of 15.9 µM and 8.7 µM, respectively, against MCF-7 and hypotriploid human cells (T47D) [151].…”
Section: Hybrid 3-phenylcoumarinsmentioning
confidence: 93%
“…Fluorinated-, 4-aminophenyl-N-phosphorylated-and N-thiophosphorylated-7-O-sulphamate-3-arylcoumarins (compounds 63, 64 and 65 respectively) have been studied by the same research group, showing more than 10 times higher inhibitory potency than coumarin-7-O-sulfamate as inhibitors of STS. Amongst the studied compounds, the most interesting proved to be compound 63, both displaying IC 50 values of 0.27 µM [148], a similar IC 50 of approximately 0.20 µM for the phosphorylated derivatives (compounds 64 and 65) [149,150]. Supported by molecular modelling techniques, fluorinated compound 66 has been designed, synthetized and then tested, proving to display an IC 50 of 0.18 µM against STS, and an IC 50 of 15.9 µM and 8.7 µM, respectively, against MCF-7 and hypotriploid human cells (T47D) [151].…”
Section: Hybrid 3-phenylcoumarinsmentioning
confidence: 93%
“…The molecular docking studies indicated that sulphamate moieties in compounds 44 and 45 were located within the STS catalytic region, while phosphoroamidate groups were within a short distance of the Arg98 residue, suggesting the presence of additional stabilising interactions. When the phosphoroamidates were replaced with thiophosphoroamidates, the next group of STS inhibitors was obtained 85 . In this case, the activity of the most active compound 46 (Table 3) (IC 50 value of 200 nM) was comparable with derivatives 44 and 45 (when evaluated in an enzymatic assay).…”
Section: Nonsteroidal Sts Inhibitors Containing Phosphorus Moietiesmentioning
confidence: 99%
“…Similar to OATPs, STS has become an active target for inhibitor synthesis, in an attempt to prevent circulating DHEAS from contributing to tumor growth [ 17 , 18 ] . As with OATPs, we propose an alternative strategy: using STS appropriated by various tumors to activate novel compounds to their tumoricidal forms [ 19 ] [Figure 2] .…”
Section: Examples Of “Kill Switch” Components Appropriated By Human T...mentioning
confidence: 99%